Cementite nano-crystallization in cold drawn pearlitic wires instigated by low temperature annealing. (15th July 2016) - Zhou, Lichu; Fang, Feng; Zhou, Xuefeng; Tu, Yiyou; Xie, Zonghan; Jiang, Jianqing
Abstract: The effects of low temperature annealing on the cementite structure and mechanical properties of cold drawn pearlitic steel wires were investigated. It was found that the thermal annealing at a temperature as low as 483 K could transform cementite in the as-drawn steel wires (ε = 2.0) from amorphous to nano-crystalline state. Against the conventional belief, the low temperature annealing treatment could simultaneously enhance the tensile strength and ductility of the cold drawn wires, for example, by 10% through the annealing treatment at 483 K. The underlying mechanisms responsible for enhanced mechanical properties were discussed, with a focus on the effects of solute carbon diffusion and cementite nanostructure. Graphical abstracts: